Group Counselling Services with Problem Solving Techniques in Improving Interpersonal Communication Skills of Students from Broken Home Family - Nani Barorah Nasution; Lilis Granella Sidabutar; Nina Afria Damayanti (Universitas Pendidikan Ganesha, 2023)
Communication between parents and adolescents is undoubtedly the most important process in forming social attitudes and behavior of children. This study aims to analyze the effect of group counselling services with problem solving towards students' interpersonal communication skills. Quantitative approach is applied using the quasi-experimental method of the one pre-test post-test group design. Ten students from broken home families in tenth grade were selected using a purposive sampling technique to involve as a subject of the study. The data were collected using a valid and reliable scale instrument developed by the researchers themselves. This scale was given to the subject before and after the treatment. Both descriptive statistics and the Wilcoxon test were employed to analyze the collected data. The analysis results show that there is a difference in score from the pre-test and post-test for 33.8. This result shows that there is an increase in students' interpersonal communication skills for 35.2% since the group counselling services with problem solving implemented to the subject. Moreover, the Wilcoxon test analysis examines that there is a change and significant effect of group counselling services with problem solving on broken home students' interpersonal communication skills since W stat > W table (21>8; p:0.05). Group guidance services using problem solving techniques have an effect on improving interpersonal communication skills of students from broken home family backgrounds. This is marked by a change in students' interpersonal communication skills that were previously low and are now increasing.